2020
DOI: 10.1111/jgs.16973
|View full text |Cite
|
Sign up to set email alerts
|

PTSD Improvement Associated with Social Connectedness in Gerofit Veterans Exercise Program

Abstract: Objective Post‐traumatic stress disorder (PTSD) is common in Veterans. Symptoms can perpetuate into late life, negatively impacting physical and mental health. Exercise and social support are beneficial in treating anxiety disorders such as PTSD in the general population, although less is known about the impact on Veterans who have lived with PTSD for decades. This study assessed associations between social connectedness, physical function and self‐reported change in PTSD symptoms among older Veterans specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Further, they found that the changes in self-competence predicted the changes in mental health measures including self-worth and hope. Additionally, a 3-month Gerofit exercise program in older Veterans significantly improved posttraumatic stress disorder symptoms, and this improvement was significantly associated with the level of social connectedness [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, they found that the changes in self-competence predicted the changes in mental health measures including self-worth and hope. Additionally, a 3-month Gerofit exercise program in older Veterans significantly improved posttraumatic stress disorder symptoms, and this improvement was significantly associated with the level of social connectedness [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study also aimed to facilitate social support, which has been found among other populations including veterans to drive the relationship between increased exercise and improved mental health. 61 Further investigation into the role of social support including the dyad relationship (i.e. emergency service and support partner) in moderating health behaviours is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…The study also aimed to facilitate social support, which has been found among other populations including Veterans to drive the relationship between increased exercise and improved mental health (60). Investigation into the resource of social support including the dyad relationship (i.e., emergency service and support partner) in moderating health behaviours is warranted.…”
Section: Discussionmentioning
confidence: 99%